Modern approaches to diagnosis and treatment of early-onset neonatal sepsis - Klymenko, Tetiana; Tsodikova, Olha; Serdceva, Elena (ScienceRise: Medical Science, 2020)
Early-onset neonatal sepsis (EOS) remains the leading cause of morbidity and mortality, especially among premature babies. Therefore, accurate diagnosis, prompt monitoring of the course of the disease and an effective therapeutic strategy are a guarantee of improving the quality of medical care for newborns, as well as an important reserve for reducing perinatal losses. The aim of the work to summarize modern views on the diagnosis and treatment of early-onset neonatal sepsis in newborns with perinatal pathology. Results and their discussion. An analytical review of modern literature data on problematic issues of EOS diagnostics is carried out. The approaches are stated and the main directions of EOS management at the present stage are formulated. It was revealed that the lack of a consensus definition of neonatal sepsis, the nonspecificity of clinical data is a limiting factor in the timely accurate identification of the septic process. Insufficient diagnostic value of existing laboratory tests leads to defects in the registry and monitoring of this disease, the inability to conduct an objective assessment of the existing epidemiological and microbiological situation in the health care system and the subsequent effective implementation of preventive measures. Conclusions. In the conditions of modern scientific realities, none of the existing laboratory tests can sufficiently reliably confirm or deny the presence of EOS in a newborn child, which determines the search for new promising laboratory tests with high diagnostic and prognostic potential. The optimal treatment strategy for newborns with EOS is broad-spectrum antibiotics. However, today the global problem of excessive irrational prescribing of antibacterial drugs is associated with the formation of multidrug-resistant strains of bacteria, as well as the development of long-term adverse effects, which requires improved diagnostic and treatment algorithms for children who are in the risk group of the development of neonatal sepsis by implementing a comprehensive approach using modern accurate tests in the dynamics of the disease